41.6k views
4 votes
Solve 4(-4x- 3)> 36

User Halest
by
5.7k points

2 Answers

6 votes

4(-4x-3)=36

We move all terms to the left:

4(-4x-3)-(36)=0

We multiply parentheses

-16x-12-36=0

We add all the numbers together, and all the variables

-16x-48=0

We move all terms containing x to the left, all other terms to the right

-16x=48

x=48/-16

x=-3

User Kunerd
by
5.2k points
7 votes

Answer:

x=3

Explanation:

Simplifying

4(4x + -3) = 36

Reorder the terms:

4(-3 + 4x) = 36

(-3 * 4 + 4x * 4) = 36

(-12 + 16x) = 36

Solving

-12 + 16x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.

-12 + 12 + 16x = 36 + 12

Combine like terms: -12 + 12 = 0

0 + 16x = 36 + 12

16x = 36 + 12

Combine like terms: 36 + 12 = 48

16x = 48

Divide each side by '16'.

x = 3

Simplifying

x = 3

User Mike Trader
by
4.9k points